Some research on the Terminologies of Physics in Uzbek language - Elmurodova Sohiba Saidmurodovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article deals with the issue of terminology of physics, its forming stages in Uzbek language and functioning in language. The application of terms is given, an attempt is made to clarify the appearance of terms in the language.